(untitled) (Research, Society and Development, 2021)
The aim of this paper is to present a teaching proposal by the usage of the analysis of popular music as research subject and as historical source. This proposal is based on the methodological and theoretical discussions of authors as Napolitano (2007, 2016), Hermeto (2012), Tatit (2004), Naves (2010); thinking of its applicability in the teaching of History by the concepts of Historical Culture (Soares, 2017; Rocha, 2014), Historical Consciousness (Rüssen, 2001) and Critical Consciousness (Freire, 2010). Furthermore, considers the integrated High School level by the concept of the Technological and Professional Education presented by Gramsci, Saviani, Frigotto, Ciavatta and Ramos. The research used a qualitative investigation by a Pedagogical Intervention (Damiani, 2012; et al., 2013), as an instrument of application and evaluation of this teaching proposal. A mini-course was offered for Integrated High School students of the Federal Institute of Education, Science and Technology of Paraíba - Campus Cajazeiras. The research indicates that ally Music and History increases the participation of the students, besides shows how the popular music can be an important component on the full education.